Increasing the load-carrying capacity of three-layer plates and shallow shells - Panteleev, A.D. (Проблемы прочности, 1985)
This article examines three-layer plates rectangular in plan and shallow shells of symmetrical construction subjected to bending by a transverse distributed load. The loadcarrying capacity of the plates and shells is evaluated by means of a generalized strength criterion. We solve the problem of finding the optimum law of variation in the thickness of the external layers of these structure. The resulting thickness distribution keeps the structures as far as possible from the limiting stress state.